Interaction of viral envelope glycoproteins with fibronectin. - Julkunen, I (1983)
An interaction between fibronectin and viral envelope glycoprotein micelles isolated from influenza A, parainfluenza 1, and mumps viruses was found by enzyme immunoassay. All three different glycoprotein micelles bound efficiently to solid-phase fibronectin. When fibronectin was permitted to bind to solid-phase viral glycoproteins, dose-dependent binding was observed. Soluble glycoprotein micelles inhibited the binding of fibronectin to immobilized glycoprotein preparations. The binding was not observed when fibronectin was pretreated with neuraminidase, suggesting that the sugar moieties of fibronectin are responsible for the affinity. This affinity may play a role in virus-cell interactions or in the opsonization of certain viruses during infection.